Income redistribution across OECD countries Main findings and policy implications - Causa, Orsetta (OECD Economic Policy Papers, 2019)
Income inequality has increased in most OECD countries over the past two decades. This is both because market incomes (wages, dividends, interest income) have become more unequally distributed, and also because redistribution through taxes and transfers has fallen. New OECD work explores cross-country evidence on trends in income redistribution since the mid-1990s to shed some light on the main drivers of the general decline